LEAPS Vaccine Incorporating HER-2/neu Epitope Elicits Protection That Prevents and Limits Tumor Growth and Spread of Breast Cancer in a Mouse Model. (26th March 2017) - Rosenthal, Ken S.; Stone, Sarah; Koski, Gary; Zimmerman, Daniel H.
Abstract : The prototype J-LEAPS T cell vaccine for HER-2/neu breast cancer (J-HER) consists of the murine HER-2/neu66–74 H-2 d CD8 T cell epitope covalently attached through a triglycine linker to the J-immune cell binding ligand (ICBL) (human β 2 microglobulin38–50 peptide). The J-ICBL was chosen for its potential to promote Th1/Tc1 responses. In this proof-of-concept study, the ability of J-HER to prevent or treat cancer was tested in the TUBO cell-challenged BALB/c mouse model for HER-2/neu-expressing tumors. The J-HER vaccine was administered as an emulsion in Montanide ISA-51 without the need for a more potent adjuvant. When administered as a prophylactic vaccination before tumor challenge, J-HER protected against tumor development for at least 48 days. Despite eliciting protection, antibody production in J-HER-immunized, TUBO-challenged mice was less than that in unimmunized mice. More importantly, therapeutic administration of J-HER one week after challenge with TUBO breast cancer cells limited the spread of the tumors and the morbidity and the mortality in the challenged mice. The ability to elicit responses that prevent spread of the TUBO tumor by J-HER suggests its utility as a neoimmunoadjuvant therapy to surgery. Individual or mixtures of J-LEAPS vaccines can be readily prepared to include different CD8 T cell epitopes to optimize tumor therapy and customize treatment for individuals with different HLA types.